Pengentasan Kemiskinan Perspektif Hadis Nabi (Studi Hadis Tematis-Kontekstualis ) - Andi Suseno (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2021)
Poverty is a problem that always haunts every human life in the world. Several negative impacts continue to appear in all parts of the world due to the problem of poverty. One of the aims of the Islamic Religion was to bring humanity to a life which is full of prosperity and out of poverty. Muhammad as a Prophet not only responded to matters relating to human relations with the Lord, but also horizontally dealt with human relations with each other. With his example and wise attitude, the Prophet Muhammad responded to the problem of poverty with several solutions. The moral perfection of the Prophet Muhammad is reflected in his hadiths, so it is interesting to be studied comprehensively. Discussing thematically and systematically the terms of poverty in hadith became a concrete step to uncover the Prophet's method of alleviating poverty. In the next step was the contextualization of the hadith as an effort to keep the sunnah of the Prophet Muhammad to remain shalih likulli zaman wal makan. Key words: poverty, Prophet’s hadith, thematic, contextualization